"If you could just see me": The construction of heterosexual men's sexual selves and the hierarchy of desirability. (March 2021) - Montemurro, Beth
Part of identity development involves the construction of a sexual self. Sexual selves are constructed based on interactions with others. Based on in-depth interviews with 59 heterosexual men between the ages of 30 and 59, I look at the way research participants defined heterosexual men's desirability through their framing of their sexual selves. I show how participants' stories revealed a link between desirability and masculinity for heterosexual men in U.S. culture. Moreover, I find that consistent with narratives of hegemonic masculinity, men were concerned with proving their desirability and hetero-masculinity through what I call "evidentiary stories." These stories focused on men's telling of how they were seen by others or in other contexts, with such accounts serving as evidence of their desirability. Through these stories, men constructed sexual selves that met (or failed to meet) dominant narratives of hetero-masculine desirability. In so doing, men also participated in the construction of a hierarchy of desirability among heterosexual men, underscoring the idea that certain men are more sought-after or valued than others—both by women partners and others at large.